Norms and gender discrimination in the Arab world - Abadeer, Adel SZ (Palgrave Macmillan, 2015)
PART I INTRODUCTION. - 1 Introduction 3. - Appendix 1.1: Lists of Countries in the Arab World 23. - PART II ANALYSIS OFNORMS AND GENDER DISCRIMINATION. - 2 Institutions and Gender Discrimination 27. - Appendix 2.1 51. - 3 Cultural Relativism and Gender-Discriminating Norms 53. - 4 The Capability Approach and Gender Discrimination 71. - 5 Norms in Collectivist versus Individualist Societies 85. - 6 Metanorms and Gender Discrimination 103. - 7 Cognitive Dissonance and Gender Discrimination 115. - 8 Norms, Status, and Individualist Goods 127. - Appendix 8.1: A Model of Allocating Status Goods between Females and Males 145. - Appendix 8.2: A Model of Allocating Collectivist-Individualist Goods 147. - 9 Measuring Gender Discrimination 149. - PART III GENDER DISCRIMINATION IN THE ARAB WORLD. - 10 Norms and Female Genital Mutilation/Cutting (FGM/C) 169. - Appendix 10.1: The Economics of FGM/C: A Simple Cost Benefit Analysis of FGM/C 189. - Appendix 10.2.1: Backward-Induction Analysis FGM/C as a Regular Norm 195. - Appendix 10.2.2: Backward-Induction Analysis of FGM/C as a Metanorm 197. - 11 Norms and Gender Violence 201. - 12 Norms and Women's Economic Rights 227. - 13 Norms and Women's Political and Legal Rights 241. - PART IV SUMMARY AND CONCLUSION. - 14 Summary and Conclusion 255